EFEKTIVITAS PELAKSANAAN PROGRAM PENILAIAN KINERJA KEPALA MADRASAH (PKKM) MENGGUNAKAN MODEL EVALUASI CIPP - Rahmatul Fajri, Laili (Manajerial | Journal Manajemen pendidikan islam, 2025)
Madrassas must be managed with a professional management system and be able to understand and meet the demands of society. This is where the role of leadership is needed. The head of the madrasah has a central role in determining the success of the implementation of education in the madrasah. The head of the madrasah not only acts as an administrative leader, but also as a manager, innovator, and motivator who is responsible for managing resources, improving the quality of learning, and ensuring the achievement of the institution's vision and mission. The effective performance of the madrasah head can create a conducive learning environment, improve the quality of education, and prepare competent students. One of the programs to improve the performance of the madrasah head is the Madrasah Head Performance Assessment Program (PKKM) which is the basis for its implementation is the Decree of the Director General of Islamic Education (Dirjen Pendis) No. 1111 of 2019. The purpose of this study was to evaluate the effectiveness of the implementation of the Madrasah Head Performance Assessment (PKKM) program using the CIPP (Context, Input, Process, and Product) evaluation model. The CIPP model not only focuses on results, but also context, input, process, and results. Therefore, the CIPP model is said to be more comprehensive compared to other evaluation models. This study was conducted using the CIPP evaluation method with data collection using observation, interviews, and questionnaires. The research sample was madrasas, especially Private Junior High Schools in Tasikmalaya City that had implemented the PKKM program several times, including madrasah principals, supervisors, teachers, and education personnel. Data analysis was carried out using quantitative and qualitative approaches and using the CIPP evaluation model. The results of the study showed that the Madrasah Principal Performance Assessment program with the CIPP model was considered effective in improving the performance of madrasah principals and the quality of madrasahs